Gustavsbergs keramikateljéer - Khudur, Abrar (My University, 2023)
For the majority of artists today their workplace, the studio, is fundamental. It is an essential space where art can be created, and sometimes even displayed to the public. Over several decades, art has been considered a growth factor for urban development both in Sweden and internationally. Yet many already existing studios are at risk of disappearing. With over 700 artists waiting for a studio in Stockholm, with a queue time of up to 30 years to be assigned one, there is an apparent need for more space. This master thesis investigates the need for additional studio space for ceramicists, with a particular focus on the ceramic process and the location Gustavsberg, Värmdö. Today approximately 113 artist, mainly ceramicists are housed in Gustavsbergs Porslinsfabrik old premises. The historic connection to the porcelain company is not only favored by locals but is also internationally acclaimed. For over 80 years, it has been a vital hub for Sweden’s leading ceramic artists and continues to make strong impressions on both domestic and international contemporary art. Today, over 120 artists are waiting for a workspace in the factory's old premises. The main objective of this research is to explore how to materialize the ceramic process through a design proposal, and to investigate how the connection between the artists’ studio and the public can be strengthened. The focus is to integrate the different stages of the ceramic production into the exhibition experience, while maintaining functional and private workspaces for the ceramicists.
Keywords: Gustavsberg, ceramic ateliers, open studio, exhibition